A study on the implementation of e-GP(Electronic Government Procurement System) in public works department: impact on present procurement practices and future scopes - Hasan, Humaira Binte (BRAC University, 2018)
This dissertation is submitted in partial fulfilment of the requirements for the degree of Masters in Procurement and Supply Management, 2016.